The APPLICATION OF COGNITIVE THERAPY THROUGH PLAY TO CHILDREN AGED 3-5 YEARS AT ORPHANAGE TERIMAKASIH ABADI: Terapi, Kognitif, Bermain Usia 3-5 Tahun - Rani Damanik; Henny Syapitri; Laura Mariati Siregar (Universitas Haji Sumatera Utara, 2021)
Masalah perkembangan kognitif anak merupakan hal yang harus diperhatikan sehingga anak memiliki kemampuan yang lebih kompleks baik kemampuan gerak kasar, gerak halus, bicara dan bahasa serta sosialisasi dan kemandirian. Dimana perkembangan kognitif merupakan kemampuan berfikir untuk menghubungkan, menilai maupun mempertimbangkan suatu kejadian atau peristiwa. Penerapan terapi kognitif melalui terapi bermain pada anak usia 3-5 tahun merupakan solusi dalam meningkatkan kognitif anak. Dengan dilakukannya terapi bermain bertujuan untuk meningkatkan kognitif dan perkembangan anak. Setelah pelaksanaan terapi bermain menghasilkan kemampuan anak dalam berfikir secara kognitif melalui mencuci tangan, tebak gambar dan mewarnai gambar. Kata Kunci : Terapi, Kognitif, Bermain Usia 3-5 Tahun ABSTRACT The problem of children's cognitive development is something that must be considered so that children have more complex abilities, both the ability of gross motion, fine motion, speech and language as well as socialization and independence. Where cognitive development is the ability to think to connect, assess or consider an event or events. The application of cognitive therapy through play therapy for children aged 3-5 years is a solution in improving children's cognitive. By doing play therapy aims to improve the cognitive and development of children. After the implementation of play therapy results in children's ability to think cognitively through washing hands, guessing pictures and coloring pictures. Keywords: Therapy, Cognitive, Play 3-5 Years Old